Individual characteristics of entrepreneurs in transition countries: The Albanian case - Areti Stringa; Saimir Sallaku; Jorida Tabaku (Contemporary Economics, 2009)
The transition process in Albania, as in other ex-communist countries, stopped the enterprise development. The increasing number of small and medium enterprises is the most promising consequence of the transition process. Several researches in western countries have demonstrated that entrepreneurship involves objective and subjective factors and is interrelated with environmental objective factors and individual subjective ones. Our research examines clear characteristics of the businesses' analysis, the performance of the entrepreneurs themselves (their background and personal characteristics), their motivation to start a business and the perceptions of the different characteristics and the aspects of the businesses they run.
Keywords: 330